Can dietary strategies in early life prevent childhood food allergy? A report from two iFAAM workshops. Issue 12 (21st November 2019) - Roberts, Graham; Grimshaw, Kate; Beyer, Kirsten; Boyle, Robert; Lack, Gideon; Austin, Moira; Garcia‐Larsen, Vanessa; Grabenhenrich, Linus; Halken, Susanne; Keil, Thomas; Madsen, Charlotte; Regent, Lynne; et al.
Abstract: Food allergy affects a small but significant number of children and adults. Food allergy is responsible for considerable morbidity and is the commonest cause of anaphylaxis in children. One of the aims of the European Union‐funded "Integrated Approaches to Food Allergen and Allergy Risk Management" (iFAAM) project was to improve our understanding of the best way to prevent the development of food allergy. Groups within the project worked on integrating the current prevention evidence base as well as generating new data to move our understanding forward. This paper from the iFAAM project is a unique addition to the literature on this topic as it not only outlines the recently published randomized controlled trials (as have previous reviews) but also summarizes two iFAAM‐associated project workshops. These workshops focused on how we may be able to use dietary strategies in early life to prevent the development of food allergy and summarized the range of opinions amongst experts in this controversial area.